Evaluating the impact of filler size and filler content on the stiffness, strength, and toughness of polymer nanocomposites using coarse-grained molecular dynamics - Weber, Felix; Steinmann, Paul; Pfaller, Sebastian; Ries, Maximilian; Dötschel, Vincent (Engineering Fracture Mechanics, 2024)
Their great versatility makes polymer nanocomposites an important class of engineering materials. In order to gain detailed insights into the nanoscale mechanisms underlying their macroscopic mechanical properties, molecular dynamics (MD) simulations are a valuable tool to complement experimental studies. In this work, we modify the analytical potential functions of an efficient bead–spring model representing a generic polymer nanocomposite to account for the breaking of covalent bonds. We perform uniaxial tensile simulations of double-notched specimens and validate the model using experimental trends for overall stiffness, strength, and toughness. First, we study the effects of sample size, notch geometry, strain rate, temperature, and molar mass for the pure thermoplastic matrix material. Second, we analyze the influence of filler size and filler content on the mechanical behavior of the polymer nanocomposite. With this study, we show that in both the development of new materials and the optimization of established materials, it is possible to gain important preliminary insights into the effects of pertinent material characteristics with a simple MD setup, which can then be further refined by increasing the complexity of the material description and the boundary condition
Keywords: Polymer nanocomposites; Modeling and simulation; Molecular dynamics; Mechanical properties; Fracture of polymers

Reactive coarse-grained MD models to capture interphase formation in epoxy-based structural adhesive joints - Dötschel, Vincent; Richter, Eva; Possart, Gunnar; Steinmann, Paul; Ries, Maximilian (European Journal of Mechanics A-Solids, 2026)
Adhesive joints offer a superior strength-to-weight ratio compared to conventional fastening methods, making them essential for achieving cost-efficiency and sustainability goals. The adherends influence the adhesive in their immediate vicinity, creating regions with altered microstructures. These regions, known as interphases, exhibit material properties that differ from those of the bulk adhesive and are not fully understood from an engineering perspective. To address this issue, we introduce a novel coarse-grained molecular dynamics (CGMD) model for adhesive joints, which aims to study the interphase formation and its resulting properties at the molecular level. We utilize a reactive epoxy model from the literature for the adhesive and implement matching aluminium substrates, along with the necessary adherend-adhesive interaction parameters. The resulting adhesive joint model allows us to investigate the formation of the adhesive's microstructure during the curing process and the mechanical properties of the joint. We conduct a parameter study on the adherend-adhesive interaction parameters, unravel the role of grafting bonds and their distribution, and examine the impact of the adhesive's thickness. Additionally, we identify an interphase based on variations in the local microstructure, estimate its size, and determine the influencing parameters. In this first contribution, we demonstrate the capabilities of our model in evaluating the mechanical behavior of the interphase, which is crucial for gaining a better understanding of adhesive joints.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Adhesive joint; Coarse graining; Interphase; Molecular dynamics; Structural adhesive